2017
DOI: 10.1111/1346-8138.13841
|View full text |Cite
|
Sign up to set email alerts
|

Internalized stigma in psoriasis: A multicenter study

Abstract: Internalized stigma is the adoption of negative attitudes and stereotypes of the society regarding a person's illness. It causes decreased self-esteem and life-satisfaction, increased depression and suicidality, and difficulty in coping with the illness. The primary aim of this study was to investigate the internalized stigma state of psoriatic patients and to identify the factors influencing internalized stigma. The secondary aim was to identify the correlation of internalized stigma with quality of life and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
117
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(131 citation statements)
references
References 29 publications
9
117
2
3
Order By: Relevance
“…Additionally, these feelings have negative effects on the mental health of those affected . In addition, studies have shown that people with lower education and lower income are at higher risk to perceive stigmatization …”
Section: Introductionmentioning
confidence: 94%
“…Additionally, these feelings have negative effects on the mental health of those affected . In addition, studies have shown that people with lower education and lower income are at higher risk to perceive stigmatization …”
Section: Introductionmentioning
confidence: 94%
“…Patients with genital psoriasis experience impairments in physical activity, personal relationships, work and school, and emotions 25. Although these patients report stigmatization, two studies indicate that patients with genital involvement experience greater feelings of stigmatization than psoriasis patients without genital lesions,31,32 while one did not 33. Two other studies demonstrated that patients with genital psoriasis or genital discomfort experienced more depressive symptoms than patients without genital symptoms 6,26…”
Section: Symptomsmentioning
confidence: 99%
“…Skin changes further arouse disgust or fear of possible infection, subsequently leading to discrimination and isolation . As a consequence of experienced discrimination, patients tend to accept and incorporate these prejudices, which affects self‐esteem as well as self‐efficacy, fosters isolation and is the origin of a negatively self‐reinforcing cycle …”
Section: Introductionmentioning
confidence: 99%